2001
DOI: 10.1089/107662901750152747
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of the Antimicrobial Susceptibility of Haemophilus influenzae, Streptococcus pneumoniae, and Moraxella catarrhalis Isolated from Patients with Community-Acquired Lower Respiratory Tract Infections in 1999 in Portugal

Abstract: A nationwide multicenter study (including 25 laboratories) of the antimicrobial susceptibility of bacterial pathogens commonly associated with community-acquired lower respiratory tract infections (LRTI), with testing undertaken in a central laboratory, was conducted in Portugal in 1999. Antimicrobial resistance in Haemophilus influenzae has not increased in the last decade. Of the 498 isolates tested, 12.4% produced beta-lactamase and >95% were susceptible to all antimicrobials except ampicillin. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The rate of clarithromycin-resistance found in this study is rather low but in one study carried out in Spain, up to 22.6% of H. influenzae isolates were resistant to this antibiotic [3]. Resistance or diminished susceptibility to such drugs has also been previously reported [3,5,6,10]. Resistance to other antibiotics not tested in the present study has been reported as low for chloramphenicol (0% in Italy and Portugal and 3.6% in Spain) [2], 3.2% in Portugal and 10.6% in Greece for tetracycline [4,6] and less than 0.3% in Spain and Italy for fluoroquinolones [1,2,5].…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…The rate of clarithromycin-resistance found in this study is rather low but in one study carried out in Spain, up to 22.6% of H. influenzae isolates were resistant to this antibiotic [3]. Resistance or diminished susceptibility to such drugs has also been previously reported [3,5,6,10]. Resistance to other antibiotics not tested in the present study has been reported as low for chloramphenicol (0% in Italy and Portugal and 3.6% in Spain) [2], 3.2% in Portugal and 10.6% in Greece for tetracycline [4,6] and less than 0.3% in Spain and Italy for fluoroquinolones [1,2,5].…”
Section: Discussionsupporting
confidence: 44%
“…Resistance or diminished susceptibility to such drugs has also been previously reported [3,5,6,10]. Resistance to other antibiotics not tested in the present study has been reported as low for chloramphenicol (0% in Italy and Portugal and 3.6% in Spain) [2], 3.2% in Portugal and 10.6% in Greece for tetracycline [4,6] and less than 0.3% in Spain and Italy for fluoroquinolones [1,2,5]. However resistance to cotrimoxazole is reported to be high in Spain (42.5%) [2], and low in Italy (9.3%) [2], Portugal (8.3%) [2], and Greece (5.3%) [4].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Serotyping was performed by the standard capsular reaction test with a chessboard system (36) and specific sera (Statens Serum Institut, Copenhagen, Denmark). Etest strips (AB Biodisk, Solna, Sweden) were used to determine the MICs for penicillin, as described previously (25), and the Clinical and Laboratory Standards Institute (CLSI) recommended breakpoints (10) were used to interpret the MICs. The isolates were further characterized by determining their susceptibilities to co-trimoxazole, levofloxacin, erythromycin, clindamycin, tetracycline, and chloramphenicol by the Kirby-Bauer disk diffusion technique, according to the CLSI recommendations and interpretative criteria (10).…”
Section: Methodsmentioning
confidence: 99%